Unveiling the Global Surge: Unraveling the Factors Fueling the Spread of Karoshi Syndrome - Al-Madhagi HA (Dove Medical Press, 2023)
Haitham Ahmed Al-Madhagi Biochemical Technology Program, Dhamar University, Dhamar, YemenCorrespondence: Haitham Ahmed Al-Madhagi, Email bio.haitham@gmail.comAbstract: Karoshi syndrome, also known as "death by overwork", has been a topic of study and concern in Japan since the 1980s. World Health Organization (WHO) and International Labour Organization (ILO) joint unveiled that in 2021, approximately 750.000 deaths due to Karoshi syndrome globally. The joint defined long working as having > 55 h work/week. Karoshi nowadays is no longer limited to Japan and has become a global issue. Karoshi is primarily attributed to factors such as long working hours, job-related stress, and poor work-life balance. This perspective was sought to provide a short overview of Karoshi syndrome, the underlying mechanisms and the state-of-art preventive measures.Keywords: Karoshi syndrome, working overload, cardiovascular diseases, stroke